Envelhecer como mulher : intersecções de gênero, idade, classe e raça nas protagonistas de Elena Ferrante - Pontel, Heloisa Maria Silveira (My University, 2026)
This dissertation discusses the representation of female aging in the work of Elena Ferrante from an intersectional feminist perspective that articulates the categories of gender, class, age, and race. Starting from the observation that aging remains marginal to literary narratives and to hegemonic feminist debates, the study analyzes the novels Troubling Love (2017), The Lying Life of Adults (2020), The Lost Daughter (2016), and The Story of the Lost Child (2023). Methodologically, the research is grounded in a bibliographic review and literary analysis anchored in intersectional feminism, highlighting aging as a category of oppression that remains underexplored. The theoretical framework is based on bell hooks's (2015) definition of oppression, as well as on studies of the categories of gender, race, class, and age by: Joan Scott (2014, 1992); Virginia Woolf (2014); Simone de Beauvoir (2019); bell hooks (2021); Angela Davis (2016); Audre Lorde (2014, 2019); Kristen R. Ghodsee (2018); Silvia Federici (2021); Susan Pickard (2016); Simone de Beauvoir (2018); and Mirian Goldenberg (2013). The analysis shows that, in Ferrante's narratives, female aging is not configured as an isolated or purely biological process, but rather as an experience deeply intertwined with gender and class-based oppressions, encompassing themes such as motherhood, the body, sexuality, work, and friendship. A significant racial erasure is also observed in the works analyzed, understood as a structural silence that limits the intersectional complexity of these representations. The study concludes that Ferrante's literature offers important contributions to contemporary feminist debate, while also highlighting the need to expand discussions of female aging toward more diverse, racialized perspectives situated outside the European axis. [resumo fornecido pelo autor]
Esta dissertação discute a representação do envelhecimento feminino na obra de Elena Ferrante a partir de uma abordagem feminista interseccional que articula as categorias de gênero, classe, idade e raça. Partindo da constatação de que o envelhecimento permanece à margem das narrativas literárias e dos debates feministas hegemônicos, o estudo analisa os romances Um Amor Incômodo (2017), A Vida Mentirosa dos Adultos (2020), A Filha Perdida (2016) e História da Menina Perdida (2023). Metodologicamente, a pesquisa se fundamenta em revisão bibliográfica e análise literária, ancoradas no feminismo interseccional, destacando o envelhecimento como categoria de opressão ainda pouco explorada. O construto teórico se baseia na definição de opressão de bell hooks (2015), bem como nos estudos sobre as categorias de gênero, raça, classe e idade de: Joan Scott (2014, 1992); Virginia Woolf (2014); Simone de Beauvoir (2019); bell hooks (2021); Angela Davis (2016); Audre Lorde (2014), Kristen R. Ghodsee (2018); Silvia Federici (2021); Audre Lorde (2019); Susan Pickard (2016); Simone de Beauvoir (2018); Mirian Goldenberg (2013). A análise evidencia que, nas narrativas de Ferrante, o envelhecimento feminino não se configura como um processo isolado ou biológico, mas como uma experiência profundamente imbricada às opressões de gênero e de classe, atravessando temas como maternidade, corpo, sexualidade, trabalho e amizade. Observa-se também o apagamento racial significativo nas obras analisadas, compreendido como um silêncio estrutural que limita a complexidade interseccional dessas representações. Conclui-se que a literatura de Ferrante oferece importantes contribuições para o debate feminista contemporâneo, bem como evidencia a necessidade de ampliar as discussões sobre envelhecimento feminino em perspectivas mais diversas, racializadas e situadas fora do eixo europeu. [resumo fornecido pelo autor]
Keywords: Análise do discurso; Ferrante, Elena, 1943-; Envelhecimento - Mulheres; Feminismo e literatura; Discourse analysis; Aging - Woman; Feminism and literature